“ARMENIAN” ELEMENT IN THE ORAL NARRATIVES OF THE AZERBAIJANIS OF NAKHCHIVAN - Baranov, Dmitrij Aleksandrovic; Sorohov, Vladimir Andreevic (History, Archeology and Ethnography of the Caucasus, 2024)
This paper aims to analyze the “Armenian” motifs found in the oral narratives of Azerbaijanis in Nakhchivan. The study is based on interviews recorded during fieldwork among Nakhchivan Azerbaijanis from 2021 to 2023. The research employs the concepts of cultural and communicative memory developed by J. Assman. The study reveals several recurring motifs in the informants’ stories: the idea of the non-indigenousness of Armenians in Nakhchivan; the “Albanization” of medieval material culture; the common ancestry of local Azerbaijanis and Armenians; memories of Armenian friends and neighbors; shared local practices and sacred places; and the motif of the “lonely elderly Armenian woman” that bridges the region’s past and present. A particularly noteworthy aspect is the concept of “kirva,” a tradition in Nakhchivan where artificial kinship is established between Armenians and Azerbaijanis for mutual support, leading to the formation of intergroup strong ties. The authors conclude that the presence of “Armenian” elements in the narratives of Nakhchivan Azerbaijanis reflects a certain “Armenian-centricity. The prominence of the “Armenian” layer in many stories might be explained by the Azerbaijani discourse’s dependence on the Armenian one, which manifests in an ongoing hidden form of dispute with competing historical narratives. In this sense, non-Azerbaijani perspectives on the region’s history and cultural heritage significantly contribute to the cultural memory of the Azerbaijanis of Nakhchivan.